Evaluation of the Lifestyle of Female High School Students Regarding Osteoporosis Prevention - Zahra Pishkar Mofrad; Fatemeh Azarkish; Alireza DashiPoor (Mashhad University of Medical Sciences, 2013)
Background: In people over 50, one out of three women and 12 men experience osteoporosis. Youth lifestyle plays an essential role in increasing bone mass and preventing osteoporosis in old ages. Thus, lifestyle changes during adolescence could cause the prevention of osteoporosis in older age. This study therefore conducted to investigate the lifestyle of female high school students in relation to prevention of osteoporosis. Methods: In this cross-sectional study 403 female students recruited from high schools in Iranshar, Iran included in the study. Data were collected using a questionnaire consisted of two parts of demographics and lifestyle issues associated with osteoporosis including nutrition, physical activity and habits. Data analysis was carried out using Chi-square and t test. Results: results showed that 57.1% of the stdents had poor nutrition. In relation to the habits including smoking, alcohol consumption, adherence to medications and weight loss regimens, 78.2% of students had a relatively favorable lifestyle. 48.1% of subjects had a desirable lifestyle in terms of physical activity.  The total score of lifestyle in 82.4% of students was relatively favorable. There was a significant relationship between lifestyle and age (P = 0.027), maternal education (P = 0.035) and occupation (P = 0.034). Conclusion: Considering that the lifestyle of more than half of the students were poor in relation to nutrition, it is suggested that in addition to giving awareness to the adolescents regarding risk factors and preventive measures of osteoporosis, families should also be taught to include calcium-rich foods in the food basket of their households.